2017
DOI: 10.1007/s00454-017-9878-7
|View full text |Cite
|
Sign up to set email alerts
|

Four Soviets Walk the Dog: Improved Bounds for Computing the Fréchet Distance

Abstract: Given two polygonal curves in the plane, there are many ways to define a notion of similarity between them. One popular measure is the Fréchet distance. Since it was proposed by Alt and Godau in 1992, many variants and extensions have been studied. Nonetheless, even more than 20 years later, the original O(n 2 log n) algorithm by Alt and Godau for computing the Fréchet distance remains the state of the art (here, n denotes the number of edges on each curve). This has led Helmut Alt to conjecture that the assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Only quite recently there has finally been progress on this question. First, Buchin et al [12] presented an algorithm with a slightly improved (but still superquadratic) running time. Then, Bringmann [7] proved that no significantly faster algorithm for computing the Fréchet distance between two general polygonal curves exists unless the Strong Exponential Time Hypothesis (SETH) fails.…”
Section: Introductionmentioning
confidence: 99%
“…Only quite recently there has finally been progress on this question. First, Buchin et al [12] presented an algorithm with a slightly improved (but still superquadratic) running time. Then, Bringmann [7] proved that no significantly faster algorithm for computing the Fréchet distance between two general polygonal curves exists unless the Strong Exponential Time Hypothesis (SETH) fails.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992 Alt and Godau [2] were the first to consider the problem and gave an O(n 2 log n) time algorithm for the problem. The only improvement since then is a randomized algorithm with running time O(n 2 (log log n) 2 ) in the word RAM model by Buchin et al [7]. In 2014 Bringmann [4] showed that, conditional on the Strong Exponential Time Hypothesis (SETH), there cannot exist an algorithm with running time O(n 2−ε ) for any ε > 0.…”
Section: Introductionmentioning
confidence: 99%
“…Another common approach is to perform a so-called image skeletonization [6,8] instead of contour selection . Computing the Frechet distance between curves, both open and closed, is a relatively well researched problem [1,3,5,7] . Since an image contour is always some sort of a curve, comparing contours with the Frechet metric does not impose much difficulty .…”
Section: Introductionmentioning
confidence: 99%